Nanomaterials to address the genesis of antibiotic resistance in Escherichia coli - Kaushik, Mahima; Sarkar, Niloy; Singh, Amit; Kumar, Pankaj (Frontiers in Cellular and Infection Microbiology, 2023)
Escherichia is a genus of prokaryotic gram-negative bacteria which forms a vital component of the gut microbiota of homeotherms including humans. Many members of this genus are commensals and pathogenic strains, which are responsible for some of the most common bacterial infections and can be fatal, particularly in the case of newborns and children. The fecal matter in wastewater treatment plants serves as major environmental sinks for the accumulation of Escherichia. The rise in antibiotic pollution and the lateral gene exchange of antibiotic-resistant genes have created antibiotic-resistant Escherichia strains that are often called superbugs. Antibiotic resistance has reached a crisis level that nowadays existing antibiotics are no longer effective. One way of tackling this emerging concern is by using nanomaterials. Punitively, nanomaterials can be used by conjugating with antibodies, biomolecules, and peptides to reduce antibiotic usage, whereas, preventatively, they can be used as either nano-antimicrobial additives or nano-photocatalytic sheets to reduce the microbial population and target the superbugs of environmental Escherichia. In this review, we have explored the threat posed by pathogenic Escherichia strains in the environment, especially in the context of antibiotic-resistant strains. Along with this, we have discussed some nanomaterial-mediated strategies in which the problem can be addressed by using nanomaterials as nanophotocatalytics, antimicrobial additives, drugs, and drug conjugates. This review also presents a brief overview of the ecological threats posed by the overuse of nanomaterials which warrants a balanced and judicious approach to the problem.